Combinatorial analysis of translation dynamics reveals eIF2 dependence of translation initiation at near-cognate codons. Issue 13 (6th July 2021) - Ichihara, Kazuya; Matsumoto, Akinobu; Nishida, Hiroshi; Kito, Yuki; Shimizu, Hideyuki; Shichino, Yuichi; Iwasaki, Shintaro; Imami, Koshi; Ishihama, Yasushi; Nakayama, Keiichi I
Abstract: Although ribosome-profiling and translation initiation sequencing (TI-seq) analyses have identified many noncanonical initiation codons, the precise detection of translation initiation sites (TISs) remains a challenge, mainly because of experimental artifacts of such analyses. Here, we describe a new method, TISCA (TIS detection by translation Complex Analysis), for the accurate identification of TISs. TISCA proved to be more reliable for TIS detection compared with existing tools, and it identified a substantial number of near-cognate codons in Kozak-like sequence contexts. Analysis of proteomics data revealed the presence of methionine at the NH2 -terminus of most proteins derived from near-cognate initiation codons. Although eukaryotic initiation factor 2 (eIF2), eIF2A and eIF2D have previously been shown to contribute to translation initiation at near-cognate codons, we found that most noncanonical initiation events are most probably dependent on eIF2, consistent with the initial amino acid being methionine. Comprehensive identification of TISs by TISCA should facilitate characterization of the mechanism of noncanonical initiation. Graphical Abstract: